Symptomatic cysts of the cavum septi pellucidi, cavum vergae and cavum veli interpositi: A retrospective duocentric study of 10 patients - Krejčí, Tomáš; Vacek, Petr; Krejčí, Ondřej; Chlachula, Martin; Szathmaryová, Silvia; Lipina, Radim (Clinical neurology and neurosurgery, 2019)
OBJECTIVE: Cysts of the Cavum septi pellucidi (CSP), cavum vergae (CV) and cavum veli interpositi (CVI) are anterior midline intracranial findings which are typically incidental - only rarely do we encounter symptomatic cysts of this type. Only a quite small number of these cysts series have been published, controversies regarding optimal management still exist. PATIENTS AND METHODS: This is a retrospective study of 10 patients treated at 2 clinics between 2002-2018. 9 patients underwent surgery and 1 is under long-term monitoring. Apart from demographic data, the study analyzed symptoms, cyst size and progression over time, ventricle size, complications, and treatment modality. RESULTS: CSP with CV was found in 8 cases with 1 case each of CSP and CVI. The study comprised 6 men and 4 women, including 4 children. The mean follow-up time was 43.4 months. The average cyst size was 20.4 mm in CSP and 19.8 mm in CV; the CVI was 33 mm. Headache was most commonly reported (70%) followed by behavioral disturbance (30%). Disturbance in memory, psychomotor development, school performance, visual acuity, and vomiting was variously noted in 20%. The prevailing symptom was headache in adults and behavioral and autonomic disturbance in children. Postoperatively, cysts had reduced by an average of 44.3% while the ventricles remained unchanged. Symptoms resolved in all cases with residual problems in patients presenting with memory loss. No complications were noted. CONCLUSION: Endoscopic fenestration is the method of choice in the treatment of symptomatic midline cysts. We recommend that any further research focuses on precisely establishing their clinical presentation, particularly neuropsychological symptoms.
Keywords: mladý dospělý; předškolní dítě; retrospektivní studie; Child; Central Nervous System Cysts; Humans; lidé; magnetická rezonanční tomografie; Retrospective Studies; mladiství; Neuroendoscopy; lidé středního věku; Septum Pellucidum; Brain Neoplasms; Magnetic Resonance Imaging; nádory mozku; Middle Aged; Female; Male; Adult; septum pellucidum; mužské pohlaví; Aged; neuroendoskopie; ženské pohlaví; Child, Preschool; Young Adult; dospělí; cysty centrálního nervového systému; dítě; Adolescent; senioři